Long‐term efficacy and safety of CT‐P13, a biosimilar of infliximab, in patients with inflammatory bowel disease: A retrospective multicenter study. Issue 9 (18th March 2019) - Kim, Nam Hee; Lee, Ji Hyun; Hong, Sung Noh; Yoon, Hyuk; Kang, Hyoun Woo; Lee, Suck‐Ho; Im, Jong Pil; Cha, Jae Myung; Eun, Chang Soo; Kim, Ji Won; Choi, Chang Hwan; Park, Dong Il
Abstract: Background and Aim: A biosimilar of infliximab, CT‐P13 (Remsima®) has the potential to reduce treatment costs and enhance access to biological therapy for inflammatory bowel disease (IBD) patients. However, long‐term clinical data on its use for IBD treatment are currently sparse. We aimed to investigate the long‐term efficacy and safety of CT‐P13 therapy in a large, real‐life IBD cohort. Methods: A total of 368 IBD patients (227 with Crohn's disease [CD] and 141 with ulcerative colitis [UC]) treated with CT‐P13 at 16 referral hospitals in Korea between July 2012 and December 2017 were retrospectively analyzed. Results: The cumulative retention rates at years 1, 3, and 5 were 86.1%, 68.5%, and 58.7% and 69.7%, 46.0%, and 26.7% in anti‐tumor necrosis factor (TNF)‐naïve CD and UC patients, respectively. The clinical response and remission rates at week 14 and at years 1, 3, and 5 were 94.3%, 92.7%, 76.8%, and 17.6% and 78.6%, 82.4%, 72.2%, and 17.6% in anti‐TNF‐naïve CD and 85.6%, 80.0%, 55.2%, and 6.7% and 42.6%, 59.8%, 44.2%, and 6.7% in anti‐TNF‐naïve UC patients, respectively. Among patients who switched from the biologic originator to CT‐P13, the cumulative retention rates at years 1, 3, and 5 were 88.5%, 66.1%, and 44.8% in CD, and 73.9%, 42.5%, and 42.5% in UC patients, respectively. Significant improvements in disease activity scores were accompanied by marked reductions in inflammatory marker levels, and no unexpected adverse events including death or malignancy occurred during the study period. Conclusions: Long‐term treatment with CT‐P13 is effective in inducing and maintaining disease improvement and is well‐tolerated in patients with IBD. CT‐P13 may be a promising treatment option for IBD.